High-Mobility Group Box-1 and Endothelial Cell Angiogenic Markers in the Vitreous from Patients with Proliferative Diabetic Retinopathy - Ahmed M. Abu El-Asrar; Mohd Imtiaz Nawaz; Dustan Kangave; Marwan Abouammoh; Ghulam Mohammad (Hindawi Limited, 2012)
The aim of this study was to measure the levels of high-mobility group box-1 (HMGB1) in the vitreous fluid from patients with proliferative diabetic retinopathy (PDR) and to correlate its levels with clinical disease activity and the levels of vascular endothelial growth factor (VEGF), the angiogenic cytokine granulocyte-colony-stimulating factor (G-CSF), the endothelial cell angiogenic markers soluble vascular endothelial-cadherin (sVE-cadherin), and soluble endoglin (sEng). Vitreous samples from 36 PDR and 21 nondiabetic patients were studied by enzyme-linked immunosorbent assay. HMGB1, VEGF, sVE-cadherin, and sEng levels were significantly higher in PDR patients than in nondiabetics (P=0.008; <0.001; <0.001; 0.003, resp.). G-CSF was detected in only 3 PDR samples. In the whole study group, there was significant positive correlation between the levels of HMGB1, and sVE-cadherin (r=0.378, P=0.007). In PDR patients, there was significant negative correlation between the levels of sVE-cadherin and sEng (r=−0.517, P=0.0005). Exploratory regression analysis identified significant associations between active PDR and high levels of VEGF (odds ratio = 76.4; 95% confidence interval = 6.32-923) and high levels of sEng (odds ratio = 6.01; 95% confidence interval = 1.25-29.0). Our findings suggest that HMGB1, VEGF, sVE-cadherin and sEng regulate the angiogenesis in PDR.